The Techniques of Guitar Playing - Josel, Seth; Tsao, Ming (Kassel Bärenreiter, 2014)
The Techniques of Guitar Playing by Seth F. Josel and Ming Tsao is a new instruction manual for guitarists wishing to improve their mastery of the variety of expressive means used in contemporary music and also for composers wanting to write for the guitar. The book is the result of a working project in artistic development with the title The Guitar as a Vehicle for New Music PerformancePractice financed by the Faculty of Fine, Applied and Performing Arts at the University of Gothenburg.This book is a fine illustration of the mission of the Academy of Music and Drama itself, balancing as it does in the borderlands between education and research. With courses at the basic level running parallel to advanced studies, development projects and research in several disciplines, the Academy offers a wealth of possibilities for motivating as well as inspiring the creation and practiceof new art.
Keywords: Method